Incredible customer service : - Freemantle, David (McGraw-Hill, 1993)
It doesn't matter how good a company's products or prices are-these days, a company must also offer incredible customer service. Freemantle provides managers with steps to implement a top-flight customer service program that includes workshops, goal-setting, audit trails, weekly reviews, brainstorming, rewards, and incentives. Emphasizing global thinking and global markets, Freemantle also presents examples and case studies of major international and local companies like British Airways, BMW, Mars Confectionary, and the Bank of Scotland